2020
DOI: 10.1002/ps.6195
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of insecticide spatial distribution within individual citrus trees and efficacy through Asian citrus psyllid reductions under different application methods

Abstract: BACKGROUND Citrus greening disease (Huanglongbing, HLB) has infected >90% of Florida's oranges and thus growers are desperate to improve pest management strategies. In this field study, insecticide application efficacy was investigated with liquid chromatography mass spectrometry to determine if insecticide concentration and distribution were effective at killing the target pest Asian citrus psyllids (ACP). Sample discs attached to leaves were sprayed with imidacloprid and malathion at a field site in Florida.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Observed differences in reported half-lives and rate constants may be due to various factors including application method, insecticide physiochemical properties and type (contact or systemic), tree canopy size (older vs younger trees), or meteorological conditions like temperature, humidity, or rainfall. The spray application method impacts coverage, and thus the insecticide concentration measured in leaf samples which could affect the rate constant when concentration-dependent (Table ). Greater tree canopy size and foliage can affect light exposure to leaf samples. ,, Thus, smaller trees, like our younger-aged trees sampled, are more likely to have less shade and moisture on leaves, and higher temperatures due to increased light exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observed differences in reported half-lives and rate constants may be due to various factors including application method, insecticide physiochemical properties and type (contact or systemic), tree canopy size (older vs younger trees), or meteorological conditions like temperature, humidity, or rainfall. The spray application method impacts coverage, and thus the insecticide concentration measured in leaf samples which could affect the rate constant when concentration-dependent (Table ). Greater tree canopy size and foliage can affect light exposure to leaf samples. ,, Thus, smaller trees, like our younger-aged trees sampled, are more likely to have less shade and moisture on leaves, and higher temperatures due to increased light exposure.…”
Section: Resultsmentioning
confidence: 99%
“…ACP data was obtained by a professional ACP inspector in the grove before and after foliar spray to compare insecticide treatments with ACP population reductions. , For each insecticide treatment, 30 rows of trees were sprayed with insecticide and inspected for ACP. ACP were counted in 3 trees in each row (the north border, middle, and south border) totaling n = 90 trees inspected for each treatment (Figure S5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease management currently depends on the efficient application and adequate distribution of insecticides to reduce the density of ACP. However, recent studies have shown that even advanced insecticide management programs fail to control the spread of HLB (Rehberg et al, 2021). The outlook for the global citrus industry is thus precarious, especially for Florida's citrus industry, which risks losing relevance and economic importance if crop yields continue to fall and trees keep dying.…”
Section: Introductionmentioning
confidence: 99%
“…Plant protection is important in the orchard production process to promote fruit production ( Zhao et al., 2017 ; Jiang et al., 2021 ), while the current means still relies on chemical spray ( Zhai et al., 2018 ; Rehberg et al., 2020 ; Zheng et al., 2020a ). It is ideal for the entire canopy of fruit trees to be uniformly covered by droplets.…”
Section: Introductionmentioning
confidence: 99%